(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
Sheep pox and goat pox (SGP) of small ruminants are most severing pox diseases of domestic animals, and they have a very important role in agricultural economy. Thereby, SGP are included in the notifiable diseases of Office International des Epizooties (OIE). Time and place distributions of these diseases are relatively stable worldwide. Transportation of infected animals could spread these viruses to the new areas. In most countries in which capripox are enzootic, vaccination and bio-security are the only two main control measures. SGP control programs have been commenced about 50 years ago in Iran, and there is a good situation for eradication of it. In this review, readers can find latest information in some essential aspects of etiology, distribution, transmission, and control of the diseases. Besides, current situation of the disease in Iran has been described, which perhaps are similar to the other endemic areas in the world. http://dx.doi.org/10.5455/javar.2015.b117